MORPHOLOGICAL CHARACTERISTICS OF POSTTRAUMATIC SKELETAL MUSCLE REGENERATION AFTER EXPERIMENTAL BLAST INJURY - N. G. Vengerovich; I. A. Shperling; Yu. V. Yurkevich; O. O. Vladimirova; I. I. Alekseyeva; A. V. Shulepov; S. G. Shchipanov; N. V. Shperling; Ye. V. Romanova (Бюллетень сибирской медицины)
The research objective was a morphological analysis of posttraumatic regeneration of musculoskeletal tissue in rats after experimental blast injury with field simulation of remote musculocutaneous injury of lower limbs. Wound process was evaluated visually and by histological characteristics of injury zones. This research helped to deepen understanding of details of regenerative process of blast musculocutaneous injury and formation of regenerating muscular and connective tissue of skeletal muscle in rats